Analysis Of Oyster Mushroom Business Development (Pleurotus Ostreatus) In Palembang City: Analisis Pengembangan Usaha Jamur Tiram (Pleurotus Ostreatus) Di Kota Palembang) - Dian Septianita (Program Studi Agribisnis Universitas Sumatera Selatan, 2021)
The development of the oyster mushroom (Pleurotus ostreatus) is quite encouraging farming mushrooms in Indonesia, both for consumption and for commercial purposes. Similarly, of Palembang City, which has a lot to cultivate oyster mushroom cultivation and is one of the villages producing oyster mushrooms – although until now not managed and cultivated to its full potential. Study was to quantify the cost of production, revenue, income and efficiency of oyster mushroom farm of Palembang City. This study was conducted in July 2021 until September 2021 in District Ilir west I of Palembang City. Site selection study conducted by (purposive). The data used are primary data and secondary data analysis of the data used is the analysis of the cost of production, revenue and revenue analysis and analysis of business efficiency. The results showed that the average size of kumbung 20.88 m2, with a production cost of Rp. 6,962,314.90 / ut, receiving Rp. 13 million, -/ut, Rp.6.037.685.10/ut revenue and R / C ratio of 1.87. Rated R / C ratio> 1 means mushroom farm in the village District Ilir west I of Palembang City efficient and profitable.